The Challenges in Maturing the Age of Marriage Among Teenagers in Bandar Village, Pacitan Regency: Reproductive Health Review - Suryani,; Dessy Elva Listianti,; Widiono Ahmad Fajri, (Indonesian Journal of Medical Anthropology, 2024)
The age of marriage is still become a dilemma for Indonesian people, especially for them who live in rural areas with a thick local wisdom. The influence of local wisdom in deciding the marriage is so great in the society so that they do not pay any respect to the regulations that have been made by the government. The impact of child marriage can affect reproductive health, which is largely ignored by society. In fact, reproductive health is one of the factors in achieving the Indonesian government’s goal to have a golden generation in 2045. However, if the society’s knowledge about reproductive health is lacking, will Indonesia really get the golden generation as it dreams of? This research wants to reveal the problems that occur in Indonesian society, especially people who are living in rural areas. Using qualitative methods, this research was conducted through several stages, one of which was literature studies and in-depth interviews. The results of the study show that there are several factors influence the challenges of maturing child marriage, such as local culture of the society, family economic conditions, and lack of knowledge about reproductive health. Due to the lack of knowledge on reproductive health, people experience vulnerability to child marriage, marriage by accident, and end up on dropping out of school. This is an urgent condition that requires serious handling by various parties through collaboration to provide information related to reproductive health and maturing the age of marriage.